Strategy! / A Business Unit Simulation: Second Edition - Priesmeyer Richard H (South-Western Publishing Co, 1992)
This book challenges you to think beyond the daily operations of business to analyze and manage strategic business issues. Overview of this Manual, Quick Reference Guide, Introduction to Strategy, Concept of Strategy Simulation, The Decision Making Cycle, Importance of Organizing Your Team, Advice from Those Who Have Gone Before, Introduction to Industries, How to Read the Enviro Scan Reports, Inter-Industry Relationships, Cost of Creating SBUs in Each Industry, Your Management Team, Organizing Your Management Team, Managing Your Team Effectively, The Strategy Planner, Performance Evaluations, The Decision Disk, A Note about Disk Handling, Introduction to the Decision Disk, Description of Main Menu Items, Developing Portfolio-Level Strategies, Establishing a Corporate Mission, Strength and Weakness and Opportunity and Threat (SWOT) Analysis, Turnaround Strategies, Developing Portfolio-Level Strategies, Budgeting SBUS and Business-Level Strategies, The Budgeting Procedure, SBU Strategies, Cash Account Management, Appendices.